A PROSPECTIVE, OBSERVATIONAL AND ANALYTICAL STUDY TO MONITOR CAESAREAN SECTION RATE IN ACCORDANCE WITH THE MODIFIED ROBSON’S TEN GROUP CLASSIFICATION - Shambhawi Kalyani; Vanita Raut (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
For nearly 30 years, the international healthcare community has considered the ideal rate for caesarean sections (CS) to be between 10% and 15%. This was based on the following statement by a panel of reproductive health experts at a meeting organized by the World Health Organization (WHO) in 1985 in Fortaleza, Brazil: “There is no justification for any region to have a rate higher than 10-15% [1]. Since then caesarean sections have become increasingly common in both developed and developing countries for a variety of reasons [2, 3]. When medically justified, caesarean section can effectively prevent maternal and perinatal mortality and morbidity [4]. However, there is no evidence showing the benefits of caesarean delivery for women or infants who do not require the procedure. As with any surgery, caesarean sections are associated with short and long term risk which can extend many years beyond the current delivery and affect the health of the woman, her child and future pregnancies. These risks are higher in women with limited access to comprehensive obstetric care [5, 6, 7] In order to propose and implement effective measures to reduce or increase CS rates where necessary, it is first essential to identify what groups of women are undergoing CS and investigate the underlying reasons for trend in different settings. This requires the use of a classification system that can best monitor and compare CS rates in a standardised, reliable, consistent and action – oriented manner. Such a classification system should be applicable internationally and useful for clinician and public health authorities. Ideally such a system should be simple, clinically relevant, accountable, replicable and verifiable. [8] Thus amongst the existing systems used to classify caesarean sections, the 10-group classification (also known as the ‘Robson classification’) has become widely used in many countries in recent years [8,9]. Proposed by Dr Michael Robson in 2001, the system stratifies women according to their obstetric characteristics, thereby allowing a comparison of caesarean section rates with fewer confounding factors. [10] Currently, there is no standard classification system for caesarean section that would allow the comparison of caesarean section rates across different facilities, cities, countries or regions in a useful and action-oriented manner. As such, it is not yet possible to exchange information in a meaningful, targeted, and transparent manner to efficiently monitor maternal and perinatal outcomes [11].